Pelatihan Pembuatan, Pengemasan, Pelabelan dan Digital Marketing Produk Turunan Minyak Atsiri di Desa Batu Sandaran - Lisa Nesti; Meilizar Meilizar; Firdaus Jamsan; Musdirwan Musdirwan; Haswan Haswan; Rahmi Elviana (Journal of Industrial Community Empowerment, 2022)
Balai Batu Sandaran Village, which is included in the administrative area of Barangin District, Sawahlunto City, West Sumatra, is one of the centers for citronella oil production in West Sumatra. In this village, a citronella oil refining industry has been established. The establishment of a citronella oil refining industry is one way that can be done so that existing citronella can be processed into essential oils. Mekar Wangi is one of the SMEs that uses essential oils as an additional ingredient in the household cleaning products they produce. The obstacles faced by Mekar Wangi in developing their business are the absence of PIRT, inadequate packaging, and difficulty in marketing. It only operates when there is an order. Through this activity, it is expected that Mekar Wangi will understand techniques to make attractive packaging and labeling so that they can be made later for the products they produce and provide understanding to the public that digital marketing needs to be done in promoting their business. The method of implementing this activity is carried out by giving technical demonstrations of making essential oil derivative products, labeling, product packaging, and digital marketing and providing entrepreneurial motivation so that they are able to compete and provide added value for the Mekar Wangi.